Explaining International Comovements of Output and Asset Returns : The Role of Money and Nominal Rigidities - Kollman, Robert (IMF Working Papers; Working Paper, 1999)
Empirically, output and asset returns are highly positively correlated across the United States and the other major industrialized countries. Standard business cycle models that assume flexible prices and wages, in the Real Business Cycle tradition, have great difficulties explaining this fact. This paper presents a dynamic-optimizing stochastic general equilibrium model of a two-country world with sticky nominal prices and wages and a flexible exchange rate. The structure here predicts positive international transmission of country-specific monetary policy and technology shocks, and it generates sizable cross-country correlations of output and of asset returns.